Understanding the probiotic health benefits of Bifidobacterium animalis subsp. lactis, BB-12™ - Collins, Fergus W. J.; Vera-Jiménez, Natalia I.; Wellejus, Anja (Frontiers in Microbiology, 2025)
Probiotics have a longstanding association with human health, yet the mechanisms behind their benefits are often unclear. To understand the mode of action for the efficacy of a probiotic, it is important to take a broad overview of the interactions between the microbe, its environment, and the host. The BB-12 Bifidobacterium animalis subsp. lactis strain is one of the most documented probiotic strains on the market and has been shown to be effective in alleviating symptoms of a low defecation frequency and infant colic, among others. In this review, we examine the wide range of preclinical and clinical data available for the strain, to help elucidate some of its potential mechanisms of action. We describe the defence mechanisms developed by the strain to ensure gastrointestinal survival and transit, as well as the current knowledge on how BB-12 interacts with the host epithelial lining and cells of the immune system and the relationship between the strain and the gut microbiota. Collectively, the well documented clinical efficacies demonstrated by BB-12 are most likely not through one single mechanism, but through the collective direct and indirect effects the strain has on both its environment and the host.